ICT in the judicial system: promising yet challenging? Part I / Zaiton Hamin & Ani Munirah Mohamad - Hamin, Zaiton; Mohamad, Ani Munirah (CMIWS and UiTM Press, 2010)
Drawn from a doctoral research, the first part of this paper aims at discussing the concept of ICT adoption in the judicial system by discussing the different applications of ICT in the courts of Malaysia and other selected jurisdictions such as the United States of America, Spain, Italy, Singapore and Australia. Apart from the concept, the benefits and advantages that could be derived from these technologies would also be reviewed. Being a double-edged sword, at one end the adoption of ICT provides considerable potentials to improve the delivery of justice. However, at the other end it raises numerous practical and administrative hurdles, as well as the issue of the acquisition of skills and readiness of the court officials, legal practitioners and litigants in embracing the technologies.